2018
DOI: 10.1007/s40641-018-0103-4
|View full text |Cite
|
Sign up to set email alerts
|

Drought, Heat, and the Carbon Cycle: a Review

Abstract: Purpose of the Review Weather and climate extremes substantially affect global-and regional-scale carbon (C) cycling, and thus spatially or temporally extended climatic extreme events jeopardize terrestrial ecosystem carbon sequestration. We illustrate the relevance of drought and/or heat events (BDHE^) for the carbon cycle and highlight underlying concepts and complex impact mechanisms. We review recent results, discuss current research needs and emerging research topics. Recent Findings Our review covers top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
115
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(130 citation statements)
references
References 191 publications
4
115
1
Order By: Relevance
“…This demonstrated that losses in net carbon uptake during the summer were largely offset by carbon gains in the extremely warm spring. This suggests that the warm spring reduced the carbon cycle dependence on timing (Sippel et al, ).…”
Section: Drought Impact On Socio‐environmental Systems and Its Mitigamentioning
confidence: 99%
See 1 more Smart Citation
“…This demonstrated that losses in net carbon uptake during the summer were largely offset by carbon gains in the extremely warm spring. This suggests that the warm spring reduced the carbon cycle dependence on timing (Sippel et al, ).…”
Section: Drought Impact On Socio‐environmental Systems and Its Mitigamentioning
confidence: 99%
“…With increasing climate change, the intensity and frequency of droughts will likely increase (Brando et al, 2019;Sippel et al, 2018). As a result, forests may lose their role as a robust sink of carbon, which will exacerbate potential warming trends (Yang et al, 2018).…”
Section: Impacts Of Drought On Carbon Cyclementioning
confidence: 99%
“…from ESMs(Anderegg et al 2013, 2015c, Kaisermann et al 2017, Sippel et al 2018. Soil moisture also regulates plant growth, and especially sap area and tree ring size on interannual time scales, with wet years leading to larger tree rings (Gao et al 2018).…”
mentioning
confidence: 99%
“…Soil freezing may also promote DOC losses (Haei et al 2010, Hagemann et al 2016 by physically disrupting soil aggregates (Kalbitz and Kaiser 2008), damaging plant roots (Cleavitt et al 2008), and lysing microbial cells (Yanai et al 2004). Similarly, drought has been linked to increased aeration of otherwise waterlogged soils, facilitating the decomposition of soil carbon and eventual DOC release (Freeman et al 2001b, Sippel et al 2018, while increased precipitation has been shown to enhance the mobilization of organic carbon from soils to streams (Ågren et al 2010(Ågren et al , de Wit et al 2016. Although these studies have shed important light on our understanding of soil carbon responses to individual drivers, they have not addressed the combined, interactive, and potentially lagged and legacy effects (Smith et al 2009) of climate extremes that typify seasonal transitions in ecosystems.…”
Section: Discussionmentioning
confidence: 99%